2018
DOI: 10.1159/000493826
|View full text |Cite|
|
Sign up to set email alerts
|

Schizandrin A Alleviates LPS-Induced Injury in Human Keratinocyte Cell Hacat Through a MicroRNA-127-Dependent Regulation

Abstract: Background/Aims: Inflammatory skin diseases are the most common problems in dermatology. Schizandrin A (SchA) has been reported to have anti-inflammatory properties. Herein, we aimed to investigate the protective effects of SchA on lipopolysaccharide (LPS)-induced injury in keratinocyte HaCaT cells. Methods: Inflammation injury in HaCaT cells was induced by LPS treatment. Cell viability, apoptotic cell rate, and apoptosis-related proteins were analyzed by cell counting kit-8 (CCK-8) assay, Annexin V-(fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…Schizandrin A (SchA), extracted from Fructus schisandra , has been proven to play effective functions in various diseases due to its biological properties (4). For example, SchA alleviated lipopolysaccharide-induced inflammatory injury in human keratinocyte HaCat cells (5). SchA increased chemosensitivity to 5-fluorouracil by upregulation of miR-195 in colon cancer cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…Schizandrin A (SchA), extracted from Fructus schisandra , has been proven to play effective functions in various diseases due to its biological properties (4). For example, SchA alleviated lipopolysaccharide-induced inflammatory injury in human keratinocyte HaCat cells (5). SchA increased chemosensitivity to 5-fluorouracil by upregulation of miR-195 in colon cancer cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exact target of Schisandrin A in OA remains to explore. A recent study revealed that miR-127 was involved in the protective roles of Schisandrin A on LPS-induced inflammation injury in HaCaT cells (Li et al, 2018), indicating the possible mechanism. In view of the promising therapeutic effects of Schisandrin A demonstrated by our research, further work is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Schizandrin A (SA) is a bioactive lignin compound isolated from Schisandra chinensis [11]. It shows several cytoprotective activities, including anticancer [12], anti-inflammatory [13], and anti-liver-injury activities [14]. In addition, it was reported that SA can improve cerebral ischemia reperfusion injury to exert neuroprotective effect [15,16].…”
Section: Introductionmentioning
confidence: 99%